Islam, Local Culture, and the Motto Maja Labo Dahu in Bima: a Foucauldian Critical Discourse Analysis of Power and Institutionalization - Muhammad Kurniansyah; Muhaemin Latif; Abdullah Thalib (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study is grounded in concerns over the transformation of local cultural values amid modernization, which may weaken their role in shaping social behavior. It examines the philosophical meaning and socio-discursive role of maja labo dahu within the Bima community of West Nusa Tenggara, Indonesia. The discussion focuses on the integration of Islam and local culture, the construction of moral discourse, and the role of power relations in sustaining social norms. This study aims to analyze (1) the philosophical values embodied in maja labo dahu, (2) its function as a dominant moral discourse from a Foucauldian perspective, and (3) the role of power relations in its institutionalization within social institutions. This research employs a qualitative approach with a critical discourse analysis framework. Data were collected through observation, interviews, and documentation, and analyzed using inductive and deductive techniques. Data validity was ensured through triangulation. The findings reveal that maja labo dahu, meaning “shame and fear,” represents a synthesis between Islamic teachings and local cultural values that forms the ethical foundation of Bima society. From a Foucauldian perspective, it functions as a dominant moral discourse reproduced through educational, religious, and governmental institutions. The study concludes that maja labo dahu is a dynamic discursive practice shaping moral subjectivity, collective identity, and social order, while reflecting the operation of power–knowledge in contemporary society.